Recreational and Touristic Activity, Forming Poltava Region in the Territory Branding Context - Borodych, Larysa; Savchenko, Oleksandr; Vasyliev, Pavlo (International Journal of Engineering and Technology, 2018)
The analysis of factors of branding of territories that is the driving force for the development of the recreational and tourist system of the Poltava region is carried out. The approaches used by the regions to create their brand strategy are analyzed. Regardless of the specific objectives, successful brand strategy strategies of territories characterized by a common partner approach have been researched. As a result of the analysis of the structure of urban planning, to identify common factors that affect both the design of urban development objects and the design of the brand territory. It is concluded that the urban construction concept is the starting impulse of the territorial branding strategy. The types of potentially attractive resources for economic development and increase of attractiveness of the region are determined. The given classification is a religious tourism based on a rather developed network of religious buildings, most of which are architectural monuments, as one of the most important at the present stage of the development of tourist infrastructure in the Poltava region. On the example of organizing a regional network of religious tourism, the feasibility of using it to increase the investment attractiveness of the region has been proved.Â Â